PERANCANGAN GLOBAL POSITIONING SYSTEM (GPS) PADA SISTEM PRESENSI ONLINE BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL - Emanuel Pabianan; Christine Dewi (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
Presence is an activity that is often carried out by students, employees and staff. The attendance methods used are quite varied, ranging from manual attendance, fingerprints, etc. This method still has shortcomings such as manual recording. This research aims to design a website-based Global Positioning System (GPS) presence system at the Center for Innovative Teaching and Learning (P3I). The design was carried out using a supporting tool, namely Entity Relationship (ERD). The research method used by the author is the waterfall method which develops systematically from one stage to another like a waterfall. The testing stage uses 2 methods, namely alpha beta testing and system testing, in alpha testing in the test results table, results are obtained if the system runs without problems and is in accordance with user needs and beta testing is testing carried out by interview while system testing is testing by distributing questionnaires to find out the level of acceptance of the attendance system. Based on the interviews conducted, it can be concluded that the online presence website is user friendly or easy to operate and is in accordance with the objectives and benefits of the research conducted. Based on research and testing carried out.